LEGAL EFFORTS OF EXECUTION APPLICATION AGAINST JOINT TREATMENT DECISIONS (Study of the Implementation of Decisions on the Decisions of Religious Courts Number: 0701 / Pdt.G / 2014 / PA.Mlg) - Tinuk Dwi Cahyani (Universitas Muhammadiyah Ponorogo, 2019)
Case Number: 0701 / Pdt.G / 2014 / PA.Mlg is the product of the Malang Religious Court which has permanent legal force. In fact, after the ruling gets permanent legal force, it is known that the parties have a joint debt which causes problems for the parties who are responsible for paying off the joint debt if the decision only regulates the share of each of these assets. The problems in this study are: 1) The judge's decision regarding the division of joint assets in terms of legal certainty and justice in the decision Number: 0701 / Pdt.G / 2014 / PA.Mlg. 2) The implementation of sharing the shared assets 3) The implementation of shared debt division if there is no decision by the judge, in fact there is a joint debt. The author uses an empirical juridical research method located in the Malang Religious Court. Primary data is obtained by interviewing the Head and the Registrar of the Malang Religious Court and the Judge who handled the case Number: 0701 / Pdt.G / 2014 / PA.Mlg and the secondary data is obtained from research and literature review which consisted of laws and other legal materials which are relevant. Regarding the opinion of the Panel of Judges on the decision of 0701 / Pdt.G /2014 / PA.Mlg it can be learned from legal considerations in the a quo decision. In general, the principles of justice and legal certainty must be upheld. Justice must be upheld in accordance with the provisions of Article 35 to 37 of Act Number 1 of 1974 concerning Marriage, Article 85 up to Article 97 of the Compilation of Islamic Law.